Plagiarism Detection System for Java Programming Assignments by Using Greedy String-Tilling Algorithm - Norulazmi, Kasim (2008)
Plagiarism is a serious problem faced by universities in the world. University Utara Malaysia, just like any other universities, also have to face this problem. Among Information Technology graduates, Java programming assignments is an essential part of learning programming as it trains the student to solve programming assignments so that they can improve their programming skills that is useful in their professional life after graduation. Unfortunately, some students resolve to copy their assignment from their friends, thus perform the act of plagiarism. For lecturers to detect plagiarism manually is tedious and time consuming, and in most cases almost impossible to be done. This project aims at developing a prototype software tool that can help lecturers detect similarities among student Java programming assignment, thus help lecturers to identify plagiarism offenders among students. The prototype system, known as Java Plagiarism Detection System (JPDS) implements the Greedy-String-Tiling algorithm to detect similarities among tokens in a Java source code files. It is hoped that this prototype will be the stepping stone for development of a more robust plagiarism detection software tool in the future.